Brief considerations on urban expansion in Latin American megacities: the case of São Paulo (Revista Espinhaço, 2020)
In 2020, there are 34 megacities distributed around the world, of which six are located in Latin American countries (UN, 2019). According to the UN (2019), megacities are classified as urban agglomerations with at least 10 million inhabitants. The objective of the article is to analyze the trends of population growth in relation to the form of urban expansion in Latin American megacities, from the case study of the core of the São Paulo megacity. We used vector data provided by the Atlas of Urban Expansion (2016) between 1991 and 2014, as well as census data (1991 to 2010) and data from the Municipality of São Paulo (2000 and 2010) at district level. It was possible to identify that most of the new areas built in São Paulo are configured as filling empty areas, being located in consolidated districts that presented lower intensities of demographic growth.
Keywords: megacities; population growth; urban expansion; Latin America